Stress-dependent opposing roles for mitophagy in aging of the ascomycete Podospora anserina - Knuppertz, Laura (Autophagy, 2017)
Mitochondrial dysfunction is causatively linked to organismal aging and the development of degenerative diseases. Here we describe stress-dependent opposing roles of mitophagy, the selective autophagic degradation of mitochondria, in aging and life-span control. We report that the ablation of the mitochondrial superoxide dismutase which is involved in reactive oxygen species (ROS) balancing, does not affect life span of the fungal aging model Podospora anserina, although superoxide levels are strongly increased and complex I-dependent respiration is impaired. This unexpected phenotype depends on functional autophagy, particularly mitophagy, which is upregulated during aging of this mutant. It identifies mitophagy as a prosurvival response involved in the control of mitohormesis, the well-known beneficial effect of mild mitochondrial oxidative stress. In contrast, excessive superoxide stress turns mitophagy to a prodeath pathway and leads to accelerated aging. Overall our data uncover mitophagy as a dynamic pathway that specifically responds to different levels of mitochondrial oxidative stress and thereby affects organismal aging.